2008
DOI: 10.1534/genetics.108.088070
|View full text |Cite
|
Sign up to set email alerts
|

Within-Generation Mutation Variance for Litter Size in Inbred Mice

Abstract: The mutational input of genetic variance per generation (s 2 m ) is the lower limit of the genetic variability in inbred strains of mice, although greater values could be expected due to the accumulation of new mutations in successive generations. A mixed-model analysis using Bayesian methods was applied to estimate s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 46 publications
2
44
0
Order By: Relevance
“…Despite its promising features, the animal model approach to estimating mutational variance has been applied on few occasions and only in highly manipulated populations (Keightley and Hill 1992;Casellas and Medrano 2008;Casellas et al 2010). Casellas and colleagues adapted the approach of Wray (1990) to estimate the mutational variance in reproductive traits in a pedigreed inbred laboratory population of mice (Casellas and Medrano 2008) and an experimental flock of sheep (Casellas et al 2010) within a Bayesian framework.…”
mentioning
confidence: 99%
“…Despite its promising features, the animal model approach to estimating mutational variance has been applied on few occasions and only in highly manipulated populations (Keightley and Hill 1992;Casellas and Medrano 2008;Casellas et al 2010). Casellas and colleagues adapted the approach of Wray (1990) to estimate the mutational variance in reproductive traits in a pedigreed inbred laboratory population of mice (Casellas and Medrano 2008) and an experimental flock of sheep (Casellas et al 2010) within a Bayesian framework.…”
mentioning
confidence: 99%
“…generation of reliable data) and statistical (i.e. appropriate analytical models and computational requirements) limitations have led to the small number of estimates of additive mutational variance (s m 2 ) in experimental species during recent decades, a few of them obtained from populations of inbred mice (Keightley and Hill, 1992;Caballero et al, 1995;Casellas and Medrano, 2008). The magnitude of this new source of additive genetic variability was reviewed by Lynch (1988) and Houle et al (1994), and they have reported a narrow range of values accounting for between 0.05% and 1% of the phenotypic variability.…”
Section: Polygenic Mutational Variancementioning
confidence: 99%
“…Of course, the contribution of one or a few new mutations in a single individual would be small or even null, but these new polymorphisms can accumulate generation by generation, maintaining a certain degree of genetic variability in our inbred strains until they are fixed or dropped off due to mating between relatives. This mainframe idea was not investigated until a recent study was carried out by Casellas and Medrano (2008) in C57BL/6J mice, which showed that , 4.5% of the total phenotypic variability for litter size was accounted for by new mutations that had accumulated during the last few generations. This result showed an astonishing amount of genetic variability, clearly impairing the genetic stability of our inbred strains.…”
Section: Polygenic Mutational Variancementioning
confidence: 99%
See 1 more Smart Citation
“…The high deviation between the two Beijing populations (Pop1 and Pop2) may result from this operation or hybridization between different populations. Recent study indicates that a continuous and unavoidable flow of genetic variability does exist in the B6 strain (Casellas & Medrano, 2008). Watkins-Chow & Pavan (2008) also predicts that genetic variations could exist within the individual frozen embryo stock which was used to replace the foundation stock every five generations to limit the genetic drift in the Jackson Laboratory (Taft et al, 2006), and persist in the population independent of any possible selection.…”
Section: Disscussionmentioning
confidence: 99%